Hydraulics and fluid mechanics : proceedings of the First Australasian Conference held at the University of Western Australia, 6th to 13th December 1962 - Silvester, Richard (Pergamon Press, 1964)
Hydraulics and Fluid Mechanics is a collection of papers from the Proceedings of the First Australian Conference held at the University of Western Australia on December 6-13, 1962 at Nedlands, Australia. This book deals with the science of hydraulics and fluid mechanics in their practical uses in industry and research. In special situations when high-pressure oil is used in mechanical equipment, hydraulic lock is preferred for valve control. This book reviews the pressure drop in the pneumatic transfer of granular solids in a pipe where a formula is derived to determine the pressure drop when.